2015
DOI: 10.1080/00914037.2015.1038821
|View full text |Cite
|
Sign up to set email alerts
|

Properties of chitosan/soy protein blended films with added plasticizing agent as a function of solvent type at acidic pH

Abstract: Pure and blends from chitosan (CH) and soy protein isolate (SPI) were produced in varying compositions (CH/SPI 75/25, 50/50, 25/75 w/w) based on the solvent type (acetic and formic acids). Glycerol was used as a plasticizer. The interactions between the two biopolymers was confirmed by FTIR and TGA, indicating miscibility and compatibility.Increasing the amount of soy protein decreased the tensile strength and absorptive properties, but improved the ability of the film to withstand thermal degradation. Blend f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Without a plasticizer, SPI-based film exhibited low strength and flexibility due to the rigid and brittle properties of protein. However, with the modification of chitosan, the TS values of SPI–CS films increased slightly, indicating that the addition of chitosan could improve the strength of SPI films slightly, which was attributed to the hydrogen bonding in the polymers [ 21 ]. Moreover, the results also showed that the EB values of composite films obviously increased from 17.63% to 62.86% with the modification of chitosan, indicating that chitosan might cause a plasticizing effect on the protein matrix [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Without a plasticizer, SPI-based film exhibited low strength and flexibility due to the rigid and brittle properties of protein. However, with the modification of chitosan, the TS values of SPI–CS films increased slightly, indicating that the addition of chitosan could improve the strength of SPI films slightly, which was attributed to the hydrogen bonding in the polymers [ 21 ]. Moreover, the results also showed that the EB values of composite films obviously increased from 17.63% to 62.86% with the modification of chitosan, indicating that chitosan might cause a plasticizing effect on the protein matrix [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…As one of the most abundant natural biopolymers, chitosan is the N -deacetylated derivative of chitin and contains β-1-4 linked 2-amino-2-deoxy- d -glucopyranose repeat units [ 17 , 18 ]. Previous studies have shown that chitosan may interact with proteins to form films with enhanced mechanical properties [ 19 , 20 , 21 ]. However, natural defects and compatibility problems of the components might limit further application of these CS/SPI composite films.…”
Section: Introductionmentioning
confidence: 99%
“…As plasticizer, 66.7% (w/w protein) glycerol was added, with the percentage here referring to the actual amount of protein in the solution. Glycerol is a commonly used plasticizer for biopolymer films (Gao et al, 2006; Aritonang and Melia, 2014; Jost et al, 2014; Jost and Langowski, 2015; Boy et al, 2016; Jost and Stramm, 2016). To avoid gel formation and to mix the components, the stirrer temperature was kept at 50°C for an additional 30 min at 200 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…However, the effectiveness of the antimicrobial activity of chitosan is highly dependent on the type of target microorganism [ 29 , 36 , 84 , 88 , 90 , 103 , 107 ]. Furthermore, the mechanisms of the antimicrobial activity of chitosan are associated with its physicochemical properties [ 4 , 37 , 43 , 90 , 103 , 108 , 109 , 110 , 111 , 112 ]. Thus, this review article highlights the antimicrobial properties of chitosan, the factors that influence its antimicrobial activity, how bacteria and fungi respond to chitosan, and what regulators are involved in this antimicrobial response.…”
Section: Introductionmentioning
confidence: 99%